2022
DOI: 10.3389/fcimb.2022.934611
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania infection-derived extracellular vesicles drive transcription of genes involved in M2 polarization

Abstract: Although it is known that the composition of extracellular vesicles (EVs) is determined by the characteristics of the cell and its environment, the effects of intracellular infection on EV composition and functions are not well understood. We had previously shown that cultured macrophages infected with Leishmania parasites release EVs (LiEVs) containing parasite-derived molecules. In this study we show that LdVash, a molecule previously identified in LiEVs from L. donovani infected RAW264.7 macrophages, is wid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Studies evaluating the role of EVs in diseases caused by protozoa, such as cutaneous leishmaniasis, are scarce, and they were regarded as the function of EVs produced and released by the Leishmania protozoa itself [ 31 , 32 , 33 ]. In this context, the current study has used nano-flow cytometry and plasma samples from CL patients and healthy individuals to elucidate the contribution of platelet-derived MVs (pMVs) in the CL pathophysiogenesis, correlating it with the acute inflammatory phase and with antimonial treatment against the pathogen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating the role of EVs in diseases caused by protozoa, such as cutaneous leishmaniasis, are scarce, and they were regarded as the function of EVs produced and released by the Leishmania protozoa itself [ 31 , 32 , 33 ]. In this context, the current study has used nano-flow cytometry and plasma samples from CL patients and healthy individuals to elucidate the contribution of platelet-derived MVs (pMVs) in the CL pathophysiogenesis, correlating it with the acute inflammatory phase and with antimonial treatment against the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no systematic studies on the roles and corresponding mechanisms of pEVs in the pathophysiology of CL, and most of the articles found on this issue focused on investigating the impact of the protozoan-derived EVs in the host immune responses [ 31 , 32 , 33 ]. In order to address this gap in knowledge, we investigated the contribution of pMVs in the pathophysiology of acute cutaneous leishmaniasis and during antimony treatment.…”
Section: Introductionmentioning
confidence: 99%
“…EVs from L. amazonensis promoted the progression of the disease by increasing the expression of IL-6 and IL-10 by naïve macrophages [ 54 ]. Recent work has shown that the EVs secreted by Leishmania -infected macrophages (LiEVs) contain parasite-derived molecules and can carry these to the liver in murine models of infection [ 59 , 60 ]. Although there was some initial evidence that LiEVs are associated with the M2 polarization of macrophages, further work is required to verify that the EVs are responsible for the alternatively activation of M2 polarization.…”
Section: Extracellular Vesicles Secreted By Protozoan Parasitesmentioning
confidence: 99%